Developing Intercultural Competence in English Language Teaching - Ashirboyeva, Zukhra (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article explains that intercultural competence is the ability for communication and effective interaction among people from various cultural backgrounds. It is not only any theorical ideas, but it shows the ability to think, feel and behave when interacting with different cultural people. In teaching, intercultural competence is essential to understand and communicate between a teacher’s and a student’s ability in a respectful way.